Early prediction of histopathological response of locally advanced rectal cancer after 1 week of preoperative radiochemotherapy using 18FDG PET-CT imaging: a prospective clinical validation study - Yulia Kundel; Zoya Cohen; Noa Gordon; Aaron Sulkes; Sara Morgenstern; Gali Perl; Nir Wasserberg; David Groshar; Hanna Bernstine; Baruch Brenner (Radiation Oncology)
Abstract Background Neoadjuvant (preoperative) radiochemotherapy (nRCT) is a standard of care in locally advanced rectal cancer (LARC). Several studies have shown that the decline in 18FDG uptake after 2 weeks of nRCT compared with the baseline, i.e. the tumor’s metabolic response, may correlate with histopathological response. However, our previous prospective study suggested that the tumor’s histopathological response could be predicted by the metabolic response already observed after 1 week of nRCT. The current study was undertaken to validate these findings. Methods Thirty-eight patients with LARC who received standard nRCT followed by radical surgery were enrolled. Metabolic response, evaluated by the percent of change in maximum standardized uptake value (ΔSUVmax%), measured by PET-CT imaging at baseline and on day 8 of nRCT, was compared with the histopathological response at surgery. Histopathological response was assessed by pathological complete response (pCR) and, when possible, by tumor regression grade (TRG). We also examined the association of baseline and second PET-CT parameters with pCR and TRG at surgery. Trial registration: 0239–07-RMC, registration date: 21/08/2007. Results Neither pCR nor TRG were associated with any change in PET-CT parameters after 1 week of treatment. Baseline metabolic tumor volume (MTV) was the only PET-CT parameter with a statistically significant association with pCR (p = 0.002), but not with TRG (p = 0.08). Conclusions A decrease in SUVmax after 1 week of nRCT for LARC failed to predict the achievement of pCR or TRG in the post-nRCT surgical specimen, underlining the importance of validation clinical trials. Nonetheless, our findings on the correlation between baseline MTV and histopathological response can, if confirmed, be a useful tool for treatment selection. Validation in a larger independent cohort is planned.